Informal Text Analytics at the Interface of Theoretical Research and Education - Sorina, Galina; ., . (International Journal of Engineering and Technology, 2018)
This article consists of a theoretical and a practical part. The theoretical part focuses on the ideas of informal text analytics (ITA) and the methodology for expert text analysis (META). I examine these ideas at the interface of theoretical research and education. I show that Aristotleâ€™s works on logic transcend formal analytics â€“ i.e. logic â€“ to enter the realm of informal analytics. I prove this hypothesis through exploring Aristotleâ€™s analysis of question and question/answer procedures (QAP). I emphasise that, when discussing the problem of formulating questions, Aristotle suggests that not only the formal procedures of proof and argumentation but also the characteristics of persons posing questions should be taken into account. The latter builds a bridge between Aristotleâ€™s vision and informal text analytics. The practical part comprises the syllabus that I prepared for a relevant course. The syllabus outlines the ways to wed both avenues of analytics.Â